2011
DOI: 10.4103/0301-4738.86311
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and epidemiological analysis of glaucoma-filtering bleb infections in a tertiary eye care hospital in south India

Abstract: Purpose:To evaluate the microbial etiology and associated risk factors among patients with blebitis following trabeculectomy.Materials and Methods:A retrospective analysis of all culture-proven blebitis was performed in patients who underwent trabeculectomy between January 2004 and December 2008. A standardized form was filled out for each patient, documenting sociodemographic features and information pertaining to risk factors. Swabbing of the infected bleb surface was performed for all suspected cases and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…A study from a Tertiary Eye Care Hospital in South India revealed Streptococcus species as the predominant isolate from blebitis associated with releasable sutures. [ 1 ] The Gram-positive organisms like Staphylococcus and Streptococcus species were the most frequent organisms isolated from bleb associated infections followed by Gram-negative organisms. [ 1 2 ] P. aeruginosa has been reported to cause bleb associated endophthalmitis with fulminant presenting features and poor visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from a Tertiary Eye Care Hospital in South India revealed Streptococcus species as the predominant isolate from blebitis associated with releasable sutures. [ 1 ] The Gram-positive organisms like Staphylococcus and Streptococcus species were the most frequent organisms isolated from bleb associated infections followed by Gram-negative organisms. [ 1 2 ] P. aeruginosa has been reported to cause bleb associated endophthalmitis with fulminant presenting features and poor visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] The Gram-positive organisms like Staphylococcus and Streptococcus species were the most frequent organisms isolated from bleb associated infections followed by Gram-negative organisms. [ 1 2 ] P. aeruginosa has been reported to cause bleb associated endophthalmitis with fulminant presenting features and poor visual outcomes. [ 2 ] However, in our patient the infection was confined to the bleb with subtle signs and responded well to the antibiotics without any intraocular spread until the clearance of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Though TRAB success rates improved with the use of antifibrotics, the rates of delayed complication rates also increased parallelly, which again questioned the efficacy of TRAB as a standard glaucoma filtering surgery [15][16][17][18][27][28][29][30]. Belyea et al studied 385 eyes that underwent TRAB with antifibrotics (MMC and 5-FU) and found an incidence of late repetitive multifocal bleb leaks in 1.8% of the eyes [15].…”
Section: How Trabeculectomy Lost the Battlementioning
confidence: 99%
“…The most common microbiological flora isolated from eyes with bleb-related infections includes Staphylococcus aureus, coagulase-negative staphylococci, Corynebacterium, and Haemophilus influenza [30].…”
Section: How Trabeculectomy Lost the Battlementioning
confidence: 99%
“…Inferior bleb placement has such a high risk of BRI4 that practice has changed to predominantly superiorly placed blebs. Other risk factors have been proposed including avascular blebs,5–7 bleb leak,8 9 blepharitis,10 5-fluorouracil,11 mitomycin C (MMC),2 12 limbus-based conjunctival flap,13 young age,4 diabetes,12 multiple filtration procedures9 and bleb manipulation 14…”
Section: Introductionmentioning
confidence: 99%